The Impact of Parents Training Program for the Psychosocial Development of Autism Spectrum Disorder Students - Arman Paramansyah; Hamzah Hamzah; Rahman Pranovri Putra; Ade Herman Surya Direja; Ahmad Zamakhsari (Journal on Education, 2023)
Every parent enjoys seeing their child's ideal development on the physical and psychological levels. The truth is that certain kids, including those with autism spectrum disorder, sometimes known as autism, are born with physical or mental disabilities. The purpose of this study is to ascertain the effects that the Parent Training Program has on the psychosocial development of autistic adolescents and how those effects are perceived. This study was carried out in one of schools in Indonesia. With the goal of determining the impact of the Parent Training Program on the psychosocial development of students with autism spectrum disorder, this study employs a descriptive qualitative research method using data collection techniques through interviews, observation, and documentation studies. Based on the research findings and the technical triangulation findings, it is clear that the Parent Training Program has an effect on the psychosocial development of students with autism. Parents who have participated in the Parent Training Program and put it into practice in their parenting can support their children's developmental stages effectively, allowing children to experience development in psychosocial aspects.